Evaluation of proteins in menu of a private company in relation to that recommended by the worker's food program (Research, Society and Development, 2020)
The food offered by a company's Food and Nutrition service is extremely important in ensuring the quality of life and productivity of the worker. The objective of this work was to analyze the quality of the menus offered by a UAN (Food and Nutrition Unit) of a company during 30 consecutive days. The PAT (Workers' Food Program) was created as a parameter, which was created with the objective of promoting the health of the employee through their food. The parameters analyzed were calories offered, menu combinations, Npu and Ndpal and Ndpal%. To find out if they were adequate, lunch that was served self-service was analyzed, with only the protein option, juices and desserts. It was concluded that the calories offered on all days were above the recommended and the Ndpal% values ​​slightly above half of the analyzed days were adequate. This suggests that the menu offered by a UAN may, instead of promoting the health of the employee, may worsen causing an increase in weight and consequently chronic non-communicable diseases.